Voltage Drop on High-Rise Buildings Using The Analytical Hierarchy Process (AHP) Method - Muhammad Benjamin Reza; Unit Three Kartini; Tri Wrahatnolo; Tri Rijanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The AHP modeling method in this study was conducted by weighting six main technical criteria: Voltage Drop Magnitude (C1), Voltage Drop Percentage (C2), Load Magnitude (C3), Distance from Source (C4), Average Current (C5), and Line Impedance (C6). The analysis results show that the most dominant factor influencing voltage drop is voltage quality, with the highest criteria weights being Voltage Drop Percentage (35.7%) and Voltage Drop Magnitude (28.3%). Based on the global score index calculation, the classification of four alternative loads is as follows: The FJM Office (A1) ranks first with a score of 50.9% and is interpreted as an "Influential" load due to its voltage drop of 5.35%, which technically exceeds the standard operational limit. The AJG Office (A2) scored 23.6%, interpreted as "Moderately Influential," while the Workshop (A4) and the Security Post Office (A3) scored 16.9% and 8.2%, respectively, interpreted as "Less Influential”.